Condition monitoring of tool performance using a machine learning-based on-machine vision system during face milling of Inconel 718 - Banda, Tiyamike (2024)
The superior properties of Inconel 718 necessitate its use in manufacturing more than 50% of aircraft engine structural components, including high-pressure compressor blades, casings, and discs. However, literature attributed the synergistic impact of these properties and process parameters as the primary cause of wear complexity, notably affecting the performance of PVD-coated carbide inserts during CNC milling of Inconel 718. Features stemming from the wear complexity include uncontrolled wear mechanisms, failure modes, and a rapid flank wear rate, serving as significant indicators of sub-optimal cutting conditions. In trying to diagnose tool wear, previous Tool Condition Monitoring (TCM) techniques could not decipher, explore, and synthesise the diverse features essential for the predictive control of tool performance in challenging CNC machining conditions. Therefore, the successful implementation of advanced feature engineering and Machine Learning (ML) models in Machine Vision-based TCM (MVTCM) offers a proactive approach in predicting and controlling the performance of PVD-coated carbide tools in challenging CNC machining domains.